Introduction to addiction : addiction, animal models, and theories - Koob, George F.; Arends, Michael A.; McCracken, Mandy; Le Moal, Michel (Neurobiology of addiction, 2019)
"Introduction to Addiction, Volume One in the series, introduces the reader to the study of neurobiology of addiction by clearly defining addiction and its neuroadaptational views. This volume includes thorough descriptions of the various animal models applicable to the study of addiction, including Animal Models of the Binge-Intoxication Stage of the Addiction Cycle and Animal Models of Vulnerability to Addiction. The book's authors also include a section on numerous neurobiological theories that aid in the understanding of addiction, including dopamine, prefrontal cortex and relapse"--